If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -10x + 1 = -11x + -10 Reorder the terms: -2 + 1 + -10x = -11x + -10 Combine like terms: -2 + 1 = -1 -1 + -10x = -11x + -10 Reorder the terms: -1 + -10x = -10 + -11x Solving -1 + -10x = -10 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. -1 + -10x + 11x = -10 + -11x + 11x Combine like terms: -10x + 11x = 1x -1 + 1x = -10 + -11x + 11x Combine like terms: -11x + 11x = 0 -1 + 1x = -10 + 0 -1 + 1x = -10 Add '1' to each side of the equation. -1 + 1 + 1x = -10 + 1 Combine like terms: -1 + 1 = 0 0 + 1x = -10 + 1 1x = -10 + 1 Combine like terms: -10 + 1 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 341788=4000000x+5000000 | | 458333=4000000x+5000000 | | (x+3)((3x^2)+8x+9)=0 | | 756565291=6000000x+20000000 | | ((5x^2)+5x+7)(8x+6)=0 | | 862201322=6000000x+20000000 | | 2X+X+2X=45 | | 970337372=6000000x+20000000 | | 918048669=6000000x+20000000 | | (x-5)((x^2)+4x-2)=0 | | 852046421=6000000x+20000000 | | 857764650=6000000x+20000000 | | (x+3)((x^2)-6x+5)=0 | | 207787982=6000000x+20000000 | | 268609822=6000000x+20000000 | | 455733462=6000000x+20000000 | | 595544718=6000000x+20000000 | | 9-256x^2=0 | | ((x^2)+x+9)(x-6)=0 | | 30x-10=40/x | | 3x+16=x-48 | | 5(w-1)=9w+3-2(-4w-5) | | 5(w-1)=9w+3-2(-4-5) | | 0=3000000x+1000000 | | ((8x^2)-2x-5)(2x+7)=0 | | 135372=4000000x+7000000 | | 8y^2-20y/4y^2-8y | | 0=4000000x+7000000 | | 19+(-6)= | | ((x^3)+(2x^2)-2)((x^3)-3x+3)=0 | | F(2)=1/x-2 | | 332556=4000000x+7000000 |